2021
DOI: 10.4018/978-1-7998-4099-2.ch007
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Transformational Leadership, Cultural Orientation, and Emotional Conflict on Innovation in Multicultural Teams

Abstract: Multicultural teams represent a key strategic action that generate significant competitive advantages and innovation. The authors address the question of how transformational leadership, cultural orientation, and emotional conflict impact on multicultural teams focused on innovation. The methodology used has a quantitative and transversal approach because the measurement is carried out in a specific moment. The sample is composed by 415 multicultural-team members working in multinational companies. Results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 112 publications
1
1
0
Order By: Relevance
“…In other words, both leaders and members agree that an orientation to collaboration and submission of individual interests for the team goals (e.g., collectivism), expectation regarding importance of positions within team hierarchy (e.g., power distance dimension), preference for achievement, competition, confrontation and individual goals and material rewards for success (e.g., masculinity dimension), and the preference to avoid working under unplanned situations or in the absence of formal rules and structures (e.g., Uncertainty avoidance) are factors that do not significantly influence the team performance. Our findings exploring the effects of cultural diversity of multicultural team performace are slight similar than previous work on multicultural team innovation ( Guzmán-Rodríguez et al, 2021 ) although in that case, Guzman-Rodriguez and colleages found than only the power distance orientation affected positively to the team innovation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In other words, both leaders and members agree that an orientation to collaboration and submission of individual interests for the team goals (e.g., collectivism), expectation regarding importance of positions within team hierarchy (e.g., power distance dimension), preference for achievement, competition, confrontation and individual goals and material rewards for success (e.g., masculinity dimension), and the preference to avoid working under unplanned situations or in the absence of formal rules and structures (e.g., Uncertainty avoidance) are factors that do not significantly influence the team performance. Our findings exploring the effects of cultural diversity of multicultural team performace are slight similar than previous work on multicultural team innovation ( Guzmán-Rodríguez et al, 2021 ) although in that case, Guzman-Rodriguez and colleages found than only the power distance orientation affected positively to the team innovation.…”
Section: Discussionsupporting
confidence: 80%
“…Cultural diversity can be defined as the set of ways of thinking, attitudes, and values that characterize the team and the product of the mixture of national cultures of its members ( Hofstede, 1980 ; Kim, 2017 ; Guzmán-Rodríguez et al, 2021 ; Stahl and Maznevski, 2021 ).…”
Section: Cultural Diversity and Multicultural Team Performancementioning
confidence: 99%